Foreign body aspiration as a cause of cryptogenic hemoptysis in a child: A case report. Issue 20 (May 2018) - Qiu, Li; Zan, Yiheng; Zhong, Lin; Liu, Hanmin; Tao, Qingfen; Chen, Lina
Abstract: Rationale: Hemoptysis is rare but potentially life-threatening condition in children. The most common cause of pediatric hemoptysis is lower respiratory tract infections. Sometimes foreign body aspiration may result in hemoptysis too. Patient concerns: A 4-year old girl suffered from recurrent cryptogenic hemoptysis for almost 2 years. Diagnoses: The wheatear was finally found to be the underlying cause. Interventions: The girl received multiple bronchoscopy. Outcomes: The girl's symptoms improved rapidly and remained well without relapse of hemoptysis. Lessons: This case indicates that foreign body aspiration should be considered in any child with recurrent cryptogenic hemoptysis and persistent focal lung injury. Multiple bronchoscopy is rational in order to find out the underlying reasons.